Associations between Prenatal Education, Breastfeeding and Autistic-Like Behaviors in Pre-Schoolers - Jing Chen; Esben Strodl; Li-Hua Huang; Jing-Yi Chen; Xin-Chen Liu; Jian-Hui Yang; Wei-Qing Chen (MDPI AG, 2021)
This study aimed to investigate the association between prenatal education and autistic-like behaviors of preschoolers as well as the mediating role of breastfeeding in their associations. A cross-sectional study via a structured questionnaire was conducted with 67,578 preschool children and parents from Longhua District of Shenzhen, China. Hierarchical logistic regression models were performed to explore the associations between maternal participation in prenatal education and autistic-like behaviors in preschoolers, as well as the mediating effect of breastfeeding in the associations. After controlling for potential confounders, logistic regression analysis indicated that maternal participation in prenatal education could significantly increase the prevalence of breastfeeding, and the strength of the association was enhanced with the increase frequency of prenatal education visits (ORs ranging from 1.191 to 1.899). While both maternal participation in prenatal education (ORs ranging from 0.732 to 0.798) and breastfeeding (OR = 0.773) were significantly associated with the lower presence of autistic-like behaviors in preschoolers. The crossover analysis indicated that children with both maternal prenatal education and breastfeeding had the lower risk of presence of autistics-like behaviors (OR = 0.569). Furthermore, mediation analysis illustrated that breastfeeding mediated the association between maternal participation in prenatal education and the presence of autistic-like behaviors in preschoolers, with a mediating effect of approximately 14.3%. Our findings suggest that maternal participation in prenatal education is significantly associated with a decreased risk of autistic-like behaviors in preschool children through increased breastfeeding in the mothers who attended prenatal education.